Environmental Attitude and Knowledge Among Community Members in Rogojampi: Implications for Community-Based Environmental Education and Spatial Planning - Rima Suwistika; Nuri Hidayati (BIOCHEPHY: Journal of Science Education, 2026)
The limited engagement of community members in addressing ecological problems is linked to the lack of environmental understanding. This study described environmental attitude and environmental knowledge among members of the Paguyuban Blok EM community in Rogojampi, compared variables by sex, and examined their relationship. A quantitative survey was conducted with 26 respondents from a population of 58,262 residents. Questionnaire data were analyzed using inferential statistics. Environmental attitude was classified as high (M = 41.81), whereas environmental knowledge was moderate (M = 36.15). Sex showed no significant association with environmental attitude (p = .401) or environmental knowledge (p = .451). Pearson correlation analysis revealed no significant relationship between environmental attitude and environmental knowledge (r = .197, p = .335). However, a Mann–Whitney U test indicated significant differences between their score distributions (Z = -2.631, p = .009). These findings highlight the need for action-based environmental education to foster behavior.